Lipomas – a health condition that cannot be ignored - Sitarz, Robert; Skierucha, Małgorzata; Jazienicki, Mieczysław; Kurylcio, Andrzej; Wierzbicki, Ryszard; Maciejewski, Ryszard; Polkowski, Wojciech P. (Family Medicine & Primary Care Review, 2016)
Background . Lipomas are the most common forms of benign soft tissue tumors. They occur as various-sized lumps that rarely transform into malignant tumors. They form as a result of a focal hypertrophy of adipose cells and are usually located subcutaneously. Generally, they are palpable through the covering tissues, soft to the touch, round or oval, painless, usually movable and covered with unchanged skin. They remain mostly asymptomatic and therefore are ignored by both patients and general practitioners. Nevertheless, growing lipomas may cause problems, mainly esthetic. However, in advanced stages, their surgical removal may even require general anesthesia. Objectives. The aim of the study was to present the results of surgical treatment of subcutaneous lipomas. Moreover, there were presented the most frequent symptoms and problems relating to growing lipomas. Material and methods . There are presented three cases of patients treated surgically due to advanced subcutaneous lipomas in the Department of Surgical Oncology of the Medical University in Lublin. Results . The patients’ medical condition remained undiagnosed and untreated for a long time. As a result, patients experienced troublesome symptoms and eventually required surgical intervention. The performed operations eased their suffering and improved their quality of life. Conclusions . Although lipomas are mostly benign, their diagnosis should be confirmed by a doctor. A full physical examination performed on a regular basis should be a strict standard, as this enables detection of even early stage lipomas.